Linear methods for summing Fourier series and approximation in weighted Lebesgue spaces with variable exponents - Jafarov, S.Z. (Український математичний журнал, 2014)
In the present work, we study the estimates for the periodic functions of linear operators constructed on the basis of their Fourier series in weighted Lebesgue spaces with variable exponent and Muckenhoupt weights. In this case, the obtained estimates depend on the sequence of the best approximation in weighted Lebesgue spaces with variable exponent. Вивчаються оцінки періодичних функцій лінійних операторiв, що побудовані на основі рядів Фур'є у зважених просторах Лебега зі змінним показником та вагою Макенхаупта. В даному випадку отримані оцінки залежать від послідовності найкращого наближення у зважених просторах Лебега зі змінним показником.